THE PROBING PROMPTING MODEL TO IMPROVE STUDENT LEARNING RESULTS IN CLASS VIII A SMP NEGERI 2 GEDEG MOJOKERTO - Sunarti Sunarti (Jurnal Scientia, 2021)
This research is a class action research conducted on the facts of class VIII A student learning outcomes SMP Negeri 2 Gedeg which is still under KKM. This study aims to determine the increase in student learning outcomes in the material substance pressure through the application of the probing prompting learning model . The research was carried out for two cycles with stages consisting of planning, implementing, observing and reflecting. The research was conducted from January to February 20 20 involving 31 students of class VIII A Gedeg 2 Public Middle School . The results showed that the application of the probing model was prompt on the subject matter of Natural Sciences substance pressure can increase student activity and student learning outcomes. The application of the probing prompting learning model can train students' independence in solving a problem, so that the teacher is not used as a learning center but the teacher is only a facilitator. In addition, through the application of the probing prompting model , it can also improve the quality of learning and student learning outcomes .